FORENSIC ANALYSIS OF VEHICLE MARKINGS: CURRENT STATUS AND POTENTIAL DEVELOPMENTS - E. Chesnokova (Теория и практика судебной экспертизы)
The author addresses the current state of affairs and future prospects and trends in the development of forensic analysis of vehicle markings.